Education for Sustainable Development Situations in the West Nusa Tenggara Province - Hari Prasetyo Sutanto (LPMPP Universitas Negeri Yogyakarta, 2017)
Abstract: This research investigates Education for Sustainable Development (ESD) implementation in local governments, educational institutions and communities in West Nusa Tenggara. This exploratory research use descriptive analysis. This research came to the conclusion that the understanding of ESD at the provincial level to the community level varies due to the lack of seriousness on the central government. Only a few programs, activities and school subjects related aspects of ESD are implemented in schools and communities in West Nusa Tenggara. However, some schools and boarding houses successfully integrate aspects of ESD into school subjects such as Biology, Geography, Art and Religion and extracurricular activities such as Scouts, Youth Red Cross and the student council. At the community level, aspects of ESD in West Nusa Tenggara much more implemented by youth organizations and local NGOs, although still running independently, sectored and minimum network. KONDISI PENDIDIKAN UNTUK PEMBANGUNAN BERKELANJUTAN DI PROVINSI NUSA TENGGARA BARAT Abstrak: Penelitian ini bertujuan mengkaji kondisi pelaksanaan Pendidikan untuk Pembangunan Berkelanjutan (PPB) di tingkat pemerintah daerah, lembaga pendidikan dan masyarakat yang ada di Nusa Tenggara Barat (NTB). Penelitian ini bersifat eksploratif dengan menggunakan analisis deskriptif. Kajian ini mendapatkan kesimpulan bahwa pemahaman terhadap PPB di tingkat provinsi hingga tingkat masyarakat berbeda-beda dikarenakan minimnya keseriusan di tingkat pemerintah pusat. Hanya sedikit program, kegiatan dan mata pelajaran sekolah yang terkait aspek-aspek PPB dilaksanakan di sekolah dan di masyarakat di NTB. Beberapa sekolah dan pesantren berhasil mengintegrasikan aspek-aspek PPB ke dalam kegiatan mata pelajaran seperti biologi, geografi, seni, dan agama, serta kegiatan ekstrakurikuler berupa Pramuka, Palang Merah Remaja dan Organisasi Siswa Intra Sekolah. Di tingkat masyarakat, aspek-aspek PPB di NTB lebih banyak dilaksanakan oleh organisasi kepemudaan dan LSM lokal meskipun masih berjalan dengan arah masing-masing secara independen, sektoral dan minim jaringan.